Bi-directional electrical recording and stimulation of the intact retina with a screen-printed soft probe: a feasibility study - Vėbraitė, Ieva; Bar-Haim, Chen; David-Pur, Moshe; Hanein, Yael (Frontiers in Neuroscience, 2024)
Electrophysiological investigations of intact neural circuits are challenged by the gentle and complex nature of neural tissues. Bi-directional electrophysiological interfacing with the retina, in its intact form, is particularly demanding and currently there is no feasible approach to achieve such investigations. Here we present a feasibility study of a novel soft multi-electrode array suitable for bi-directional electrophysiological study of the intact retina. Screen-printed soft electrode arrays were developed and tested. The soft probes were designed to accommodate the curvature of the retina in the eye and offer an opportunity to study the retina in its intact form. For the first time, we show both electrical recording and stimulation capabilities from the intact retina. In particular, we demonstrate the ability to characterize retina responses to electrical stimulation and reveal stable, direct, and indirect responses compared with ex-vivo conditions.These results demonstrate the unique performances of the new probe while also suggesting that intact retinas retain better stability and robustness than ex-vivo retinas making them more suitable for characterizing retina responses to electrical stimulation.